Ajaran Tasawuf dan Tokoh-Tokohnya - Ilham; Muhammad Amri; Indo Santalia (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Sufism is part of the Islamic syari'at whose teachings are more focused on purification of the soul in order to achieve closeness, love, and unity with Allah as its creator. Historically Sufism can be divided into several periods, namely the formation period, the development period, the consolidation period, the philosophical period, and the purification period. From these several periods it can be seen that there were two streams in Sufism, namely semi-falsafi Sufism which later became philosophical Sufism and Sunni Sufism. These two streams then colored the world of Sufism. Sunni Sufism is categorized as conscious Sufism, in which the understanding of Sufism is explained simply, so that it can be understood and understood by all groups. The teachings in Sunni Sufism are more directed towards behavior that is in accordance with the Qur'an and the Sunnah of the Prophet Muhammad, so that to become a Sufi candidate one must understand the Shari'ah very well. Meanwhile, philosophical Sufism bases its teachings more on reason and feeling (dzauq), but that does not mean abandoning Shari'at, these two schools of Sufism (Sunni and Falsafi) both prioritize Shari'at, it's just that the understanding of Sufism in Falsafi flow is rather complicated to be understood by humans in general, because the expressions used are vague (syathahiyyat) and contain symbolic elements, their Sufis also experience ecstasy (spiritual intoxication).